A New Pyramid Model of Empathy: The Role of ICTs and Robotics on Empathy - Drigas, Athanasios; Papoutsi, Chara (International Journal of Online and Biomedical Engineering (iJOE), 2023)
Empathy and compassion have become a major focus for international research and appear to be important concepts in human development. There are several definitions and models of empathy and compassion available in the literature. Based on theoretical foundations, a new model of empathy – compassion - love is proposed in the present article. This new model emphasizes the evolution of the concept of empathy, which, at higher levels, takes the form of compassion, which will then be transformed into even higher universal love making empathy and compassion a creative and significant process for the gradual evolution of individuals. In addition, emphasis is placed on ICT tools that contribute to the development of empathy and compassion.